Pengaruh Diet Tinggi Fruktosa Terhadap Resistensi Insulin Pada Tikus Jantan Putih (Rattus norvegicus) Galur Wistar - Susilawati, Elis; Levita, Jutti; Susilawati, Yasmiwar; Sumiwi, Sri Adi (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2024)
High fructose intake can cause metabolic disturbances leading to the onset of metabolic syndrome and type 2 diabetes mellitus. This study will present some of the effects of fructose consumption. This study aims to model the animal test by giving 60% fructose to insulin resistance. The research method used 8 male white rats of Wistar strain which were grouped into 2 groups, namely normal group and 60% fructose group. Parameters observed on body weight, blood glucose levels, Insulin Tolerance Test Constant (ITTC), adiponectin levels and TNF-α levels and adipose tissue histology. The results showed that the administration of 60% fructose for 60 days showed a difference for blood glucose levels starting on days 30-60, ITTC values of the fructose group were smaller than the normal group, adiponectin levels of the fructose group were smaller than the normal group, while TNF-α levels of the fructose group were greater than the normal group and there was an enlargement of the diameter of white adipose tissue and a reduction in brown adipose in the fructose group, but there was no difference in body weight. It can be concluded that the administration of 60% fructose for 60 days can be used as modeling of insulin resistance test animals.